A coupling of three quadratic maps - Rech P.C.* (2009)
We consider a system of three coupled quadratic maps, being two of them periodic, and the third chaotic. We investigate, via numerical simulations, phenomena associated with the variation of the coupling parameter. Lyapunov exponents, three-dimensional phase-space plots, and bifurcation diagrams are used to characterize the several features observed as the coupling parameter is changed. © 2008 Elsevier Ltd. All rights reserved.